(3HZjI GdWGdH aj eYQaI GdeaQhV hGdhGLHs - (3GdLfGMj, GdfLaj, GdeGdcj, LYaQ Hf NVQ cGTa GdZWGA, J (B1226(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj ZeQ GdNdGFb HGdfYe(B... (3CeG HYO, aEfj UfYJ QSGdI eNJUQI dHjGf CMcGe GdTQjYI(B...s
(3BNQgG (B:s
(3hLH Ydjge PcQ GdQhGjGJ GdeaSQI hHjGf MLjJgG heYGfjgG (B...s
(3JHUQI GdeDda (B:s
(3aj SfI haGJg GNJdGa(B: 1228(3, h(B: 1227(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B491s
(3GdCYdGe(B: (3L(B2(3, U(B124s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B491s
Keywords: (3abg GdePGgH GdCNQis